De Novo transcriptome combined with physiological analyses revealed key genes for cadmium accumulation in Zhe-Maidong (Ophiopogon japonicus) - Zhao, Qian; Li, Qing; Lin, Shuting; Hou, Ruijun; Liu, Jianying; Tao, Yachen; Li, Ye; Zhou, Yifeng; Ye, Zihong; Yu, Xiaoping; Huang, Jun (Frontiers in Plant Science, 2022)
Introduction Cadmium (Cd) is a toxic heavy metal that severely threatens safe food production. Zhe-Maidong, a well-known Chinese traditional herbal medicine, is susceptible to Cd stress. However, the characteristics of Cd transformation and migration, as well as the regulatory system for genes conferring Cd accumulation of Zhe-Maidong, remains an essential issue to be addressed. Methods Zhe-Maidong seedling growth in Cd-contaminated and uncontaminated soil was conducted for 90 days. The Cd concentration was determined by inductively coupled plasma-mass spectrometry, and the Cd2+ fluorescence probe detected Cd distributions. The root transcriptome of Zhe-Maidong was then evaluated using various Cd stress hydroponic treatments designated Cd-0, Cd-M, and Cd-H. Results and discussion The enrichment factor (EF) value in the root was four times that of the leaves, indicating that the root has a high ability to absorb and accumulate Cd. The Cd2+ were mainly distributed in the root hair and the epidermis in both roots and leaves, revealing that the epidermal cells of roots may collect Cd2+ and also have an outstanding role in Cd2+ uptake. A total of 50 DEGs involved in Cd translocation and accumulation were identified. Among these DEGs, ANN, ABCC2/4, HMA1- 5, and CCX gene expression were positively correlated with EF-root, EF-leaf, EF-total, Cd-leaf, Cd-root, and Cd-plant, indicating their role in Cd transport and accumulation under Cd-stress. These data could be helpful in uncovering the Cd accumulation characteristics in Zhe-Maidong, as well as provide a bioinformatic foundation for investigations on finding gene functions and the screening of candidate genes related to Cd accumulation.